1995
DOI: 10.1002/1097-0142(19950601)75:11<2693::aid-cncr2820751109>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Influence of smoking on the development of lung metastases from breast cancer

Abstract: Background. This study examined the association between cigarette smoking status and the development of lung metastases in a group of 835 women diagnosed with primary malignant unilateral breast cancer. Method. Female patients with breast cancer diagnosed between 1982 and 1991 at Roswell Park Cancer Institute (RPCI) in Buffalo, New York, who provided information on their cigarette smoking history at the time of their diagnosis were included. The subsequent disease status of patients was monitored by the RPCI T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 14 publications
4
23
0
Order By: Relevance
“…Manjer et al found that the relative risk of death from breast cancer was 2.14 (95% CI = 1.47-3.10) in current smokers, after adjustment for age and stage and other potential confounders [29]. Scanlon et al found that, after adjustment for age, stage, and body weight, those with more than 20,000 packs over their lifetime had a relative risk of lung metastases of 3.73 (95% CI = 1.6-8.9) compared to non-smokers [30]. Fentiman et al found in women with stage I-II breast cancer that, after age and stage, smoking was the most important predictor of breast cancer specific and overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…Manjer et al found that the relative risk of death from breast cancer was 2.14 (95% CI = 1.47-3.10) in current smokers, after adjustment for age and stage and other potential confounders [29]. Scanlon et al found that, after adjustment for age, stage, and body weight, those with more than 20,000 packs over their lifetime had a relative risk of lung metastases of 3.73 (95% CI = 1.6-8.9) compared to non-smokers [30]. Fentiman et al found in women with stage I-II breast cancer that, after age and stage, smoking was the most important predictor of breast cancer specific and overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in experimental models, pulmonary inflammation is a risk factor for metastases to the lung (9, 10). Cigarette smoking, a well established cause of pulmonary inflammation (11), has been associated with both breast cancer metastasizing to the lung and increased mortality in observational studies (1214)…”
Section: Introductionmentioning
confidence: 99%
“…In cross-sectional studies, Daniell et al found that smokers with breast cancer had more and larger lymph node metastases than nonsmokers, after controlling for primary tumor size and other variables. 5,6 A case-control 7 and a retrospective cohort study 8 also found smoking to be associated with an increased risk of developing metastases to the lung. However, these studies could not definitively distinguish lung metastases from primary lung cancers.…”
mentioning
confidence: 99%